Making visual literacy meaningful in a rural context: an action research case study - Mbelani, Madeyandile (Rhodes University, Faculty of Education, Department of Education, 2007)
This thesis reports on a collaborative action research case study into the teaching of visual literacy to Grade 10 learners in a rural high school in the Eastern Cape, South Africa. Visual literacy is one of the critical aspects that have been incorporated in the teaching of English First Additional Language as required by the National Curriculum Statement (Grade 10-12), which has been implemented in Grade 10 as from 2006. With the aim of improving learners' performance in visual literacy I designed a visual literacy unit that consisted of lesson plans running over 7 periods in 10 school days. In implementing the unit the learners were first grouped and then exposed to visual grammar and visual texts and then they critically viewed such texts and designed their own. Data was collected daily in the form of individual learner journals, researcher's journal/diary, and copies were kept of activities done by learners (individually or in groups). Also, two teachers were invited as non-participant observers to each visit a lesson. Learner focus groups were conducted and critical friends were interviewed, tape recorded and transcribed. A camera was used to take still photographs to show learner activities in groups and during group presentations. The data revealed that visual literacy could be taught meaningfully in a rural high school as the learners could identify, cut, paste and discuss elements of visual language and they finally designed their own advertisements in groups. In the analysis of data the following factors emerged as hindrances for successful teaching of visual literacy in a rural high school: lack of resources; learners' lack of a foundation in visual literacy from Grades 7-9; and problems revolving around time management and pacing. As action research comes in spirals, this research represented the first one and the researcher found the study an eye opener and a foundation to build on in the second spiral (that is not part of this research).
Keywords: Visual literacy -- Study and teaching (Secondary) -- South Africa -- Eastern Cape -- Case studies Education -- Research -- Case studies Education -- Research -- South Africa -- Eastern Cape Rural schools -- Research -- Case studies Rural schools -- South Africa -- Eastern Cape